Ethics and Mental Retardation
XVI, 259 p.
Keywords: This volume offers a collection of writings on ethical issues regarding retarded persons. Because this important subject has been generally omitted from formal discussions of ethics, there is a great deal which needs to be addressed in a theoretical and critical way. Of course, many people have been very concerned with practical matters concerning the care of retarded persons such as what liberties, entitlements or advocacy they should have. Interestingly, because so much practical attention has been given to issues which are not discussed by ethical theorists, they offer a rare opportunity to evaluate ethical theories themselves. That is, certain theories which appear convincing on other subjects seem implausible when they are applied to reasoned and com pelling views we hold concerning retarded individuals. Our subject, then, has both practical and conceptual dimensions. More over, because it is one where pertinent information comes from many sources, contributors to this volume represent many fields, including philosophy, religion, history, law and medicine. We regret that it was not possible to include more points of view, like those of psychologists, sociologists, nurses and families. There is however, a good and longstanding literature on mental retardation from these perspectives.